Benzene promotes microbial Fe(III) reduction and flavins secretion. (1st November 2019) - Liu, Shan; Liu, Hui; Wang, Zhu; Cui, Yanping; Chen, Rong; Peng, Zhaofeng; Yuan, Songhu; Shi, Liang
Abstract: The microbial reduction of Fe(III) (oxyhydr)oxide is widespread in subsurface and plays a critical role in both the biogeochemical cycle of iron and the fate of contaminants. Monocyclic aromatic compounds are ubiquitous constituents of organic matter in many geologic environments and contaminated subsurface. Benzene is a typical monocyclic aromatic compound and frequently occurs in the subsurface environment. Due to its carcinogenicity and cytotoxicity, benzene may be toxic to the coexisted Fe(III)-reducing bacteria and thereby inhibit the microbial Fe(III) reduction. However, there is limited knowledge about the impact of the coexisting monocyclic aromatic compounds on the microbial Fe(III) reduction. In this study, the reduction of ferrihydrite by the dissimilatory iron-reducing bacterium Shewanella oneidensis MR-1 (MR-1) was investigated in the presence of benzene. Results showed that benzene had a negligible impact on the growth, cell morphology and integrity of MR-1, but it promoted the microbial Fe(III) reduction. The promotion of microbial Fe(III) reduction is maximum at benzene concentration of 3.8 μM. In the presence of 3.8 μM benzene, the produced Fe(II) from microbial Fe(III) reduction in 60 h doubled that in the absence of benzene, and the Fe(II)-O content of mineral surface after reduction experiment increased 4.73%. The promotion of microbial Fe(III) reduction was ascribed to the benzene induced increase of cell membrane permeability, which facilitated extracellular electron transfer and the secretion and release of flavin mononucleotide (FMN) as electron shuttle or cofactor. The impacts of benzene on the FMN secretion and microbial Fe(III) reduction have broad implications for both the cycling of iron and the biogeochemical transformation of redox-sensitive elements and contaminants in the benzene-containing subsurface environments.